51st AIAA Aerospace Sciences Meeting Including the New Horizons Forum and Aerospace Exposition 2013
DOI: 10.2514/6.2013-48
|View full text |Cite
|
Sign up to set email alerts
|

DPW-5 Analysis of the CRM in a Wing-Body Configuration Using Structured and Unstructured Meshes

Abstract: Two general purpose Reynolds Averaged Navier-Stokes (RANS) flow solvers, OVERFLOW and BCFD, are used to analyze the NASA Common Research Model (CRM) in a wing-body configuration. The codes are run on structured and unstructured common grid families built specifically for the 5 th AIAA CFD Drag Prediction Workshop (DPW-5) allowing for meaningful comparison of data. There are six grid sizes in the family ranging from a 0.6 million cell "Tiny" mesh up to a 138 million cell "Super-Fine" mesh. Results from a grid c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 18 publications
(12 reference statements)
0
8
0
Order By: Relevance
“…9 For improved prediction of turbulent normal stress anisotropy near viscous walls, which is considered responsible for secondary corner flow phenomena, the Quadratic Constitution Relation (QCR) extension 10 is applied. Yamamoto et al 11,12 and Sclafani et al 13 have shown that the flow separation in the wing-fuselage intersection of NASA's CRM configuration, which is predicted by CFD but was not observed in the experiments, will be suppressed by QCR.…”
Section: Cfd Solver and Settingsmentioning
confidence: 93%
“…9 For improved prediction of turbulent normal stress anisotropy near viscous walls, which is considered responsible for secondary corner flow phenomena, the Quadratic Constitution Relation (QCR) extension 10 is applied. Yamamoto et al 11,12 and Sclafani et al 13 have shown that the flow separation in the wing-fuselage intersection of NASA's CRM configuration, which is predicted by CFD but was not observed in the experiments, will be suppressed by QCR.…”
Section: Cfd Solver and Settingsmentioning
confidence: 93%
“…The CRM is a large, swept-wing transport similar to existing commercial wide-body aircraft. A body of literature for the CRM is available in the public domain including the model geometry, 2 computational results, 3,4,5,6,7 and experimental data. 8,9 Figure 1 shows the full configuration of the CRM including the wing, body, horizontal tail, and nacelle-pylon group.…”
mentioning
confidence: 99%
“…Computational system DELL T7500 workstation with two Intel (R) Xeon (R) -X5650 six-core processors at 2.67 GHz In Figure 7.87 the refined coarse mesh density and predicted dimensionless pressure contours on the aircraft surface are illustrated, demonstrating their qualitative agreement with those of other solvers [Lee10,Mav10]; similarly to the WB aircraft and independently of the mesh density no significant wingbody juncture separation was observed, while the same stands for horizontal tail-body juncture separation (probably due to the SST turbulence model utilized [Scl13]). Figures 7.88-7.101 contain the pressure coefficient distributions at different wing and horizontal tail span-wise sections for the initial coarse, the refined coarse, the initial medium and the refined medium mesh, compared to those of the study of Lee-Rausch et al [Lee10]; in Figures 7.88-7.90 and 7.95-7.101 the distributions, derived by the initial grids (coarse and medium) are not contained, as they are the same to those of the corresponding refined ones.…”
Section: Crm Wing-body-horizontal-tail (Wbht) Aircraft Configurationmentioning
confidence: 54%
“…Computational system DELL T7500 workstation with two Intel (R) Xeon (R) -X5660 six-core processors at 2.80 GHz No considerable wing-body juncture separation at the upper side of the wing was observed, similarly to some of the participants of the DPW's [Cez13,Par13,Sca13,Scl13]; its absence might derive from the utilization of a relatively coarse mesh along with the SST turbulence model [Scl13]. Figures 7.70 up to 7.75 contain the pressure coefficient distributions at different wing span-wise sections of the aircraft, compared to the corresponding experimental and reference calculated ones [Sca13].…”
Section: Crm Wing-body (Wb) Aircraft Configurationmentioning
confidence: 99%
See 1 more Smart Citation